2018
DOI: 10.1097/txd.0000000000000756
|View full text |Cite
|
Sign up to set email alerts
|

Improved Cuff Technique and Intraoperative Detection of Vascular Complications for Hind Limb Transplantation in Mice

Abstract: BackgroundVascularized composite tissue allotransplantation (VCA) from a cadaveric donor has now become a clinical reality and the treatment modality of choice for patients with devastating injuries, deformities, and complex tissue defects. However, many VCA patients experience severe toxicities due to the strong immunosuppression required secondary to high antigenicity of the grafts. To improve immunosuppressive protocols for VCA, feasible and reliable preclinical models are necessary. The purpose of this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Our previous work has established a reliable and consistent platform using a pre‐clinical murine model of hind limb VCA 37 to investigate novel therapies to prolong transplant survival. The transplanted graft consisted of skin, fat, muscle, bone and blood vessels (Figure S2A ), a complex combination of tissues similar to those which are often used in VCA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous work has established a reliable and consistent platform using a pre‐clinical murine model of hind limb VCA 37 to investigate novel therapies to prolong transplant survival. The transplanted graft consisted of skin, fat, muscle, bone and blood vessels (Figure S2A ), a complex combination of tissues similar to those which are often used in VCA.…”
Section: Resultsmentioning
confidence: 99%
“…as described in our previous published work. 37 Briefly, a donor's abdominal aorta and femoral vein were used for revascularization with a recipient's common carotid artery and external jugular vein, respectively, using a non‐suture cuff technique. We used BALB/c background strain as donors and C57BL/6 background strain as recipients because we have revealed that a BALB/c strain had a higher anatomical mutation rate on the Circle of Willis than C57BL/6 strain.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…66 Sucher reported 62% success rates in orthotopic models and 90% in heterotopic models. 40 Kim et al 41 modified the cuff technique and used the abdominal aorta for anastomosis because its diameter is 2-3 times larger than the femoral artery. These publications present an elegant solution for super-microvessel (0.2-0.4 mm) anastomosis and renewed interest in mouse VCA models.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, studies utilizing cuff techniques for vascular anastomoses in rodent orthotopic models have reported significantly reduced ischemic time for the procedure, offering another possible avenue for researchers interested in full hind limb transplantation. 40,41…”
Section: Heterotopic Modelsmentioning
confidence: 99%